2017
DOI: 10.1186/s13620-016-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of Mycobacterium avium subspecies paratuberculosis in dairy cattle in Xinjiang, Northwest China

Abstract: Background Mycobacterium avium subspecies paratuberculosis (MAP) causes chronic, wasting, and progressive enteritis in cattle, bringing significant economic losses in livestock industries. MAP has spread worldwide mainly due to movement of animals. The objective of this study was to determine the MAP seroprevalence in cattle in the Xinjiang Uygur Autonomous Region, Northwest China, and evaluate the difference between intensive farming herds (cattle number in a herd is more than 200, and the cattle cannot have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
14
2
Order By: Relevance
“…The seroprevalence investigation indicated that 66.7% (6/9) of herds and 14.2% of animals were positive for MAP antibodies, which is higher than the findings from previous studies from Shandong [18] and other provinces in China [41][42][43][44]. These studies recorded MAP antibodies in 2.8%-18% of animals [41][42][43][44]. However, we noted significant variation in the prevalence of MAP among the different farms, with percentages of seropositive samples ranging from 6.9% to 42.2%.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The seroprevalence investigation indicated that 66.7% (6/9) of herds and 14.2% of animals were positive for MAP antibodies, which is higher than the findings from previous studies from Shandong [18] and other provinces in China [41][42][43][44]. These studies recorded MAP antibodies in 2.8%-18% of animals [41][42][43][44]. However, we noted significant variation in the prevalence of MAP among the different farms, with percentages of seropositive samples ranging from 6.9% to 42.2%.…”
Section: Discussioncontrasting
confidence: 71%
“…The seroprevalence investigation indicated that 66.7% (6/9) of herds and 14.2% of animals were positive for MAP antibodies, which is higher than the findings from previous studies from Shandong [18] and other provinces in China [41][42][43][44]. These studies recorded MAP antibodies in 2.8%-18% of animals [41][42][43][44].…”
Section: Discussionmentioning
confidence: 76%
“…This prevalence (20.52%) was slightly lower than the 22% seroprevalence among dromedary camels in the Canary Islands, Spain (Mentaberre et al, 2013), but higher than that in sika deer (17.64%) in China (Meng et al, 2015). The MAP seroprevalence in this study was much higher than the 11.79% reported dairy and beef cattle in northern and northeastern China, 4.8% in dairy cattle in China (Sun et al, 2015;Liu et al, 2017), 3.3% in cattle in Korea (Lee and Jung, 2009), 0.84% in Mongolian cattle in Mongolia (Ochirkhuu et al, 2015), and 0.3% in saiga antelope in Kazakhstan (Orynbayev et al, 2016). Transmission of MAP is mainly through ingestion of milk and faeces contaminated with pathogens.…”
Section: Resultscontrasting
confidence: 64%
“…The study here, which makes use of passive surveillance activities routinely and voluntarily performed by dairy herds, represents an attempt to identify the characteristics associated with seropositive animals in a high herd-prevalence setting. The small proportion of positive test results (4.9%) and large proportion of positive farms (55.4%; CI 95% : 51.7–59.0%) is similar to figures obtained in previous studies, typically only a small portion of the animals in a herd test positive in serology-based results and hence individual seroprevalences are usually in the range of 3 to 10% [ 29 32 ], indeed other large serological studies perform outside U.S. reported occurrences of 2.3% and in a larger study MAP ranged from 5.6% in 2008, and 3.8% in 2015, peaking at 7% in 2009% both Denmark studies [ 33 , 34 ], finally in China a 4.8% prevalence was reported using IDEXX ELISA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%